2017
DOI: 10.1111/ans.14177
|View full text |Cite
|
Sign up to set email alerts
|

Who, where, what and where to now? A snapshot of publishing patterns in Australian orthopaedic surgery

Abstract: BackgroundDevelopment of core research competency is a principle of orthopaedic surgical training in Australia. This paper aims to provide an objective snapshot of publications by Australian orthopaedic trainees and surgeons, to contribute to the discussion on how to identify and build on research capability in the Australian Orthopaedic Association (AOA).MethodsBy analysing journals with a journal impact factor >1 from 2009 to 2015, data were gathered to explore scientific journal publications by Australian o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Furthermore, the research requirements of the orthopaedic Surgical Education and Training (SET) program could be met through presentation alone, leaving little incentive for trainees to publish their research. This is supported by an analysis of Australian orthopaedic research which reported that only 5% of publications authored by a trainee are published without a consultant surgeon as co‐author, and even less involve more than one trainee 38 . This highlights the importance of senior surgeon support for trainees wishing to conduct research during the training program, particularly for first‐author publications.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the research requirements of the orthopaedic Surgical Education and Training (SET) program could be met through presentation alone, leaving little incentive for trainees to publish their research. This is supported by an analysis of Australian orthopaedic research which reported that only 5% of publications authored by a trainee are published without a consultant surgeon as co‐author, and even less involve more than one trainee 38 . This highlights the importance of senior surgeon support for trainees wishing to conduct research during the training program, particularly for first‐author publications.…”
Section: Discussionmentioning
confidence: 91%
“…This is supported by an analysis of Australian orthopaedic research which reported that only 5% of publications authored by a trainee are published without a consultant surgeon as co‐author, and even less involve more than one trainee. 38 This highlights the importance of senior surgeon support for trainees wishing to conduct research during the training program, particularly for first‐author publications. Senior surgeons should be encouraged to create opportunities for trainees to take the lead on research projects and provide support and resources to encourage presentation and publication of trainee‐led research.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been a number of studies looking at the research output of various surgical specialties such as plastic surgery, orthopaedic surgery and surgical oncology, [2][3][4][5][6] no study to date has assessed the research output of a cohort of surgeons as well as individual surgeons. In this study, we quantified the amount and type of research being published by a subset of Australasian (Australia and New Zealand) colorectal surgeons.…”
Section: Review Of Research Output Of Australian and New Zealand Colorectal Surgeons Over The Past 20 Yearsmentioning
confidence: 99%
“…2 , 3 There have been several high-evidence publications by Australasian vascular surgeons over the past two decades, such as the GALA 4 and COBEST 5 trials, which have had significant impact on clinical practice. There has been some limited data regarding the academic output of other medical cohorts in Australasia, 68 including orthopaedic surgery and general practice. 68 Internationally, there are also several studies investigating publication trends in plastic surgery, otolaryngology and cardiac surgery among other specialties.…”
Section: Introductionmentioning
confidence: 99%
“…There has been some limited data regarding the academic output of other medical cohorts in Australasia, [6][7][8] including orthopaedic surgery and general practice. [6][7][8] Internationally, there are also several studies investigating publication trends in plastic surgery, otolaryngology and cardiac surgery among other specialties. [9][10][11] As of yet, no quantitative assessment of research output has been published in the area of vascular surgery.…”
Section: Introductionmentioning
confidence: 99%